Fanatisme dalam Interaksi Parasosial: Studi Budaya Konsumsi Blink Indonesia dalam Pembelian Merchandise Blackpink di Aplikasi Weverse dan Weverse Shop - Aurielle Thevannie The; Gabriela Laras Dewi Swastika (Journal of Management and Bussines (JOMB), 2024)
This research aims to understand the consumption behavior of Blackpink merchandise by Indonesian BLINKs through the Weverse and Weverse Shop applications. This research method uses a descriptive quasi-qualitative approach to explain fanaticism in BLINK Indonesia's parasocial interactions at Weverse Shop. The theories used include parasocial interaction theory, communication theory via computer-based media (CMC) and new media, as well as uses and gratifications theory. Data collection was carried out through interviews and online document studies with BLINK Indonesia who are active in the Weverse and Weverse Shop applications. The results of this research reveal that BLINK Indonesia develops parasocial interactions that produce fanaticism towards Blackpink, both as fans, admins and buyers at Weverse Shop. The conclusion is that the use of social media, in this case Weverse, has the potential to give rise to fanaticism in purchasing Blackpink merchandise. Keywords: Fanaticism, Computer-Mediated Communication, Parasocial Interaction, Uses And Gratifications, New Media, Weverse Blackpink